Conceptualizing safer sex in a new era: Risk perception and decision-making process among highly sexually active men who have sex with men - Nicklas Dennermalm; Kristina Ingemarsdotter Persson; Sarah Thomsen; Birger C. Forsberg; Helle Mølsted Alvesson (Public Library of Science (PLoS), 2022)
Background Men who have sex with men (MSM) are at the epicenter of the HIV epidemic. Efforts to prevent sexually transmitted infections (STIs) and HIV transmission have traditionally focused on condoms and abstinence from high risk sexual practices. Recently, additional methods such as pre-exposure prophylaxis (PrEP) and viral load sorting have been introduced. The aim of this study was to gain understanding about risk management and risk perception strategies for HIV among highly sexually active Swedish MSM with men in Berlin. Methods Eighteen sexually active Swedish MSM who travelled to or lived in Berlin were recruited and interviewed in this study. The data were analyzed using content analysis. Results and discussion These men represent a group of knowledgeable MSM in terms of HIV. They acknowledged that having sex with men in Berlin was linked to high sexual risk taking due to the higher prevalence of HIV/STIs than in Sweden, but reported that they nevertheless did not alter their risk management strategies. The analysis resulted in a conceptual model of risk assessment that allows for a deeper understanding of the complexity of the risk reduction decision-making process. Three ontological perceptions of risk were identified: accepting, minimizing and rejecting risk. Seven practiced risk reduction methods were described. Some informants applied their preferred method or set of methods to all settings and partners, while others faced complex decision-making processes. Conclusion HIV is integrated into the core of MSM's sexuality, independently of how they ontologically related to the idea of risk. A constant navigation between pleasure, risk and safety, alongside having to relate to risk created a complex process. Efforts were made to remove HIV from their lives by rejecting the idea of risk, and thereby reject the idea of the homosexual body being a possible vessel for a virus and an epidemic.